Overview of the nutritional status of selected micronutrients in Mexican children in 2006 Estado nutricional de algunos micronutrientes en niños mexicanos en 2006 - Teresa Shamah-Levy; Salvador Villalpando; Alejandra Jáuregui; Juan A. Rivera (Instituto Nacional de Salud Pública, 2012)
OBJETIVE: To present an overview of micronutrient status of Mexican children in 2006. MATERIALS AND METHODS: Data on iron, zinc, folate and vitamin B12 deficiencies and low serum copper and magnesium were gathered and critically analyzed from the 2006 National Health and Nutrition Survey. RESULTS: Iron deficiency is still the main nutritional deficiency in children (13%-26%). Zinc deficiency was high in all age groups (≈25%) but reduced 5.6 PP in children <5 y from 1999 to 2006. Folate deficiency was 3.2% and vitamin B12 deficiency 7.7% in children. Low serum magnesium and copper were high (22.6% and 30.6%, respectively). CONCLUSIONS: The prevalence of iron deficiency seems to be lowering, and zinc deficiency has reduced in Mexican children. A high prevalence of copper and magnesium deficiencies warrants further research on their public health implications. OBJETIVO: Presentar un panorama del estado de micronutrimentos de niños mexicanos en 2006. MATERIAL Y MÉTODOS: Los datos sobre deficiencias de hierro, zinc, folatos, vitamina B12 y concentraciones bajas de cobre y magnesio se analizaron a partir de la Encuesta Nacional de Salud y Nutrición 2006. RESULTADOS: La deficiencia de hierro fue la más importante en niños (13-26%). La deficiencia de zinc fue alta en todos los grupos de edad (≈25%) y disminuyó entre 1999 y 2006 5.6 pp en niños. La deficiencia de folatos fue de 3.2% y la de vitamina B12 de 7.7%. Las concentraciones bajas de magnesio y cobre fueron altas (22.6 y 30.6%, respectivamente). CONCLUSIONES: La deficiencia de hierro pareció disminuir y la de zinc se redujo en niños mexicanos. La alta prevalencia de deficiencias de cobre y magnesio merecen más investigación para entender sus implicaciones en salud pública.